2023
DOI: 10.1021/acs.jpca.2c07469
|View full text |Cite
|
Sign up to set email alerts
|

Electron Attachment to Wobble Base Pairs

Abstract: We have analyzed the low-energy electron attachment to wobble base pairs using the equation of motion coupled cluster method and extended basis sets. A doorway mechanism exists for the attachment of the additional electron to the base pairs, where the initially formed dipole-bound anion captures the incoming electron. The doorway dipole-bound anionic state subsequently leads to the formation of a valence-bound state, and the transfer of extra electron occurs by mixing of electronic and nuclear degrees of freed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…153 Our recent works have demonstrated the existence of doorway mechanisms for the formation of a stable VB state of various model systems of DNA in the gas phase and under microsolvation. 128,132,[148][149][150]156 For the GC base pair, we have used the same diabatization scheme employed by Sommerfeld to obtain the coupling between DB and VB states. The W was found to be 12 meV which is 1 order of magnitude less than the vertical excitation energies at the equilibrium geometries of the diabatic states, which means that the anionic states are in the threshold of the weak coupling limit.…”
Section: State In Deamentioning
confidence: 99%
“…153 Our recent works have demonstrated the existence of doorway mechanisms for the formation of a stable VB state of various model systems of DNA in the gas phase and under microsolvation. 128,132,[148][149][150]156 For the GC base pair, we have used the same diabatization scheme employed by Sommerfeld to obtain the coupling between DB and VB states. The W was found to be 12 meV which is 1 order of magnitude less than the vertical excitation energies at the equilibrium geometries of the diabatic states, which means that the anionic states are in the threshold of the weak coupling limit.…”
Section: State In Deamentioning
confidence: 99%
“…We have recently shown that the doorway mechanism is a general pathway for electron attachment to DNA model systems. 23,25,60,61 The doorway mechanism has also been observed for nucleobases and base pairs in the condensed phase, where the water-bound state acts as the doorway state. 25,62,63 The role of water in the electron attachment process to nucleobases has also been highlighted by Matsika and co-workers.…”
Section: Introductionmentioning
confidence: 87%
“…He showed that initial electron attachment to uracil and 5-chlorouracil in the gas phase leads to the formation of a dipole-bound state, which acts as a doorway for electron capture. , The dipole-bound state subsequently gets converted into a valence-bound state, and a cut through the adiabatic potential energy surface corresponding to the transition showed an avoided crossing between the ground and the first excited state of the radical anion. We have recently shown that the doorway mechanism is a general pathway for electron attachment to DNA model systems. ,,, The doorway mechanism has also been observed for nucleobases and base pairs in the condensed phase, where the water-bound state acts as the doorway state. ,, The role of water in the electron attachment process to nucleobases has also been highlighted by Matsika and co-workers. , The formation of a stable anion through the doorway mechanism may be competitive to the resonance-based dissociative electron attachment to DNA …”
Section: Introductionmentioning
confidence: 90%